2011
DOI: 10.1111/j.1532-5415.2011.03386.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Drug Burden Index and Falls in Older People in Residential Aged Care

Abstract: DBI is significantly and independently associated with falls in older people living in RACFs. Interventional studies designed for this population are needed to determine whether reducing DBI, through dose reduction or cessation of anticholinergic and sedative drugs, can prevent falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
184
7
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(205 citation statements)
references
References 25 publications
12
184
7
2
Order By: Relevance
“…T 20,2016 Thirty-nine participants (85%) reported having had a DXA scan within the last 5 years before the current study, with nearly equal prevalence in each group (Table II). Thirty-three patients (72%) were actively taking calcium and vitamin D supplements, and 4 patients (9%) were actively taking prescription medication for osteoporosis, again with no differences between groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T 20,2016 Thirty-nine participants (85%) reported having had a DXA scan within the last 5 years before the current study, with nearly equal prevalence in each group (Table II). Thirty-three patients (72%) were actively taking calcium and vitamin D supplements, and 4 patients (9%) were actively taking prescription medication for osteoporosis, again with no differences between groups.…”
mentioning
confidence: 99%
“…Specific medications known to contribute to falls in this population did not differ significantly among the groups, including diuretics for treatment of hypertension (12 patients in the fracture group compared with 14 patients in the control group; p = 0.532), hypoglycemic agents for diabetes mellitus (3 patients in the fracture group compared with 1 patient in the control group; p = 0.608), and psychoactive Flow diagram demonstrating the selection of patients for the fracture group. 1178 medications (7 patients in the fracture group compared with 6 patients in the control group; p = 0.743) 19,20 . The fracture group and the control group did not differ in their prevalence of potential musculoskeletal confounders (p = 1.00 for both) in the lower extremity (4 patients in the fracture group compared with 3 patients in the control group) or spine (4 patients in the fracture group compared with 3 patients in the control group).…”
mentioning
confidence: 99%
“…Anticholinergic drugs have the potential to trigger serious adverse effects, particularly among the elderly, such as falls, cognitive dysfunction and delirium [1][2][3][4][5][6][7][8][9][10][11]14 . They also contribute to increased mortality in this age group 1,3,6,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Anticholinergic drugs often have adverse effects on elderly persons [1][2][3][4] . However, they are part of the drug treatment of several situations and diseases, such as urinary incontinence and Parkinson's disease, which are common among this age group 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This medication review should be particularly focused on benzodiazepines, other psychotropic medications, and medicines that contribute to a high drug burden index (ie, those with anticholinergic or sedative properties). 6,[32][33][34] Other interventions to prevent falls have been multifactorial in nature and have addressed risk factors pertaining to the individual (eg, strength and balance training) as well as his or her ability to safely interact with the environment. A meta-analysis by Cameron et al 35 reported that multifactorial interventions reduce falls and risk of falling in hospitals and may do so in nursing care facilities.…”
Section: Nonpharmacologicalmentioning
confidence: 99%